2020
DOI: 10.7717/peerj.8861
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability in snow cover over the Xinjiang Uygur Autonomous Region, China, from 2001 to 2015

Abstract: Xinjiang, China, is a typical arid and semi-arid region of Central Asia that significantly lacks freshwater resources, and the surface runoff in this region is mainly supplied by mountain glacier and snow cover meltwater. Based on the above background and issues of transnational water resources between Xinjiang and Central Asia along the Silk Road Economic Belt, which were highlighted in the major strategy of “The Belt and Road”, this study analysed the spatial and temporal variations in snow cover and snow co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The amount of snow cover is large in winter but little distribution in high altitude mountainous areas in summer. Chen et al [43] and Li et al [68] analyzed the relationship between snow cover and altitude, and showed that the distribution of snow cover had a clear positive correlation with altitude, we also obtained an correlation coefficient 0.76 in northern Xinjiang, China. Based on multivariate data fusion method among MODIS version 5 snow products, the advanced microwave scanning radiometer for earth observing system daily snow water equivalent products and IMS products, the analyses of the snow cover changes in northern hemisphere show that SCD of Altay Mountain and Tianshan Mountain is significantly reduced [32].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The amount of snow cover is large in winter but little distribution in high altitude mountainous areas in summer. Chen et al [43] and Li et al [68] analyzed the relationship between snow cover and altitude, and showed that the distribution of snow cover had a clear positive correlation with altitude, we also obtained an correlation coefficient 0.76 in northern Xinjiang, China. Based on multivariate data fusion method among MODIS version 5 snow products, the advanced microwave scanning radiometer for earth observing system daily snow water equivalent products and IMS products, the analyses of the snow cover changes in northern hemisphere show that SCD of Altay Mountain and Tianshan Mountain is significantly reduced [32].…”
Section: Discussionsupporting
confidence: 67%
“…Yang et al [42] analyzed the change of snow cover in northern Xinjiang with site data, showing that snow cover increased from 1961 to 2017. Chen et al [43] used MODIS 8-day synthetic product to analyze the correlation between snow cover and elevation in Xinjiang, China, and there are some other studies about the snow cover variation in Tianshan Mountains [44][45][46]. However, systematic analysis of the spatial and temporal variation of snow cover in northern Xinjiang, China, is still rare, and current analyses are mainly based on the site data and MODIS version 5 snow products.…”
Section: Introductionmentioning
confidence: 99%
“…Northern Xinjiang is located in the TCZ, and snowmelt is an important source of fresh water in this region (Chen et al, 2020;Wu et al, 2021). This study showed that between 1951 and 2017 the mean annual snowmelt runoff ratios in the third-level basins in Northern Xinjiang were above 10% and exceeded 30% in some basins.…”
Section: Northern Xinjiangmentioning
confidence: 73%
“…2 of 8 typical glaciers in the middle Tianshan mountains retreated at a mean rate of < 5 m/year between 1963 and 1986, and between 1986 and 2000, seven of those glaciers retreated at a mean rate of 10–15 m/year ( Sun & W, 2006 ). The snow cover area in Xinjiang has declined significantly in recent years ( Chen, Li & Hui, 2017 ; Haidi, Zhongqin & Mingjun, 2018 ). The water surface area, water depth, and water volume of lakes at high-altitudes may see a decline in the future as mountain glaciers and snow continue to melt.…”
Section: Discussionmentioning
confidence: 99%